2022
DOI: 10.3390/cells11121901
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing on Circulating Tumor DNA in Advanced Solid Cancer: Swiss Army Knife for the Molecular Tumor Board? A Review of the Literature Focused on FDA Approved Test

Abstract: FDA-approved next-generation sequencing assays based on cell-free DNA offers new opportunities in a molecular-tumor-board context thanks to the noninvasiveness of liquid biopsy, the diversity of analyzed parameters and the short turnaround time. It gives the opportunity to study the heterogeneity of the tumor, to elucidate complex resistance mechanisms and to adapt treatment strategies. However, lowering the limit of detection and increasing the panels’ size raise new questions in terms of detection of inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Furthermore, it has been suggested that both the specific sequences, mutations and methylation profiles observed in cfDNA can serve as indicative biomarkers of cancer (8,9). In line with this, there are already FDA-approved linear cfDNA testing methods for specific alleles (reviewed in (10)), indicating the potential of cfDNA as a tool in disease diagnostics and monitoring.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, it has been suggested that both the specific sequences, mutations and methylation profiles observed in cfDNA can serve as indicative biomarkers of cancer (8,9). In line with this, there are already FDA-approved linear cfDNA testing methods for specific alleles (reviewed in (10)), indicating the potential of cfDNA as a tool in disease diagnostics and monitoring.…”
Section: Introductionmentioning
confidence: 91%
“…The panels designed for ctDNA detection use barcode enrichment to identify rare DNA sequence alterations. Both panels can detect a rare pathogenic variant with the variant allele frequency (VAF) ranging from 0.40% to 0.82% and a probability of 95% ( Vasseur et al, 2022 ). The panels have additional benefits by detecting CNVs important for the diagnosis of glioma ( Jonsson et al, 2019 ; Sharaf et al, 2021 ) except for Guradant360 CDx.…”
Section: The Market For Glioma Molecular Profilementioning
confidence: 99%
“…The variety of the parameters tested with sensitivity and specificity (single nucleotide variations (SNV), fusion genes, copy number alterations, tumor mutational burden, microsatellite status, tumor fraction (TF)) 9 vouches for the clinical applicability of cfDNA technology in the field of precision oncology and immunotherapy. FDA recently approved two next-generation sequencing (NGS) large cancer-related genes panel (large CGP) on circulating cell free DNA (cfDNA): FoundationOne® Liquid CDx (Foundation Medicine, Inc; Cambridge, MA) and Guardant360® CDx (Guardant Health, Inc.; Redwood, CA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Besides it’s utilization in the clinical setting, these characteristics make liquid biopsy a useful tool for molecular tumor boards and clinical trials inclusion 9 11 as an excellent complement to tissue biopsy 12 , still considered the gold standard. Clinical trials increasingly allow the use of liquid biopsy only as a screening tool for trial eligibility.…”
Section: Introductionmentioning
confidence: 99%